Bidentate Lewis Acid Catalyzed Inverse-Electron-Demand Diels–Alder Reaction for the Selective Functionalization of Aldehydes - Schweighauser, Luca; Bodoky, Ina; Kessler, Simon N.; Häussinger, Daniel; Wegner, Hermann A. (Synthesis, 2012)
The inverse-electron-demand Diels–Alder (IEDDA) reaction catalyzed by a bidentate Lewis acid was applied to enamines generated in situ from aldehydes. In general, a high functional group tolerance has been observed. Side reactions during the enamine forming step can limit the yield of the desired naphthalene. For citronellal as substrate, the initial intermediate after the catalyzed IEDDA reaction was trapped by an intramolecular Diels–Alder reaction to furnish a tricyclic compound. This scaffold represents the framework of natural products such as valerianoids A–C or the patchouli alcohol.
Keywords: aldehydes; catalysis; Diels–Alder reaction; fused-ring systems; Lewis acids